Usability evaluation of finger-based interaction using touch screen mobile phones: an empirical study / Alif Faisal Ibrahim - Ibrahim, Alif Faisal (2010)
Nowadays, mobile technologies have definitely become an essential part of our personal life. The use of mobile phones with touch screen has become a phenomenon among mobile consumers today, especially among teenagers and young adults. As a result, new interaction techniques which are based on the nature of touch were born. User experience is also important to ensure the success of marketing products such as mobile phones (Tobias and Spiegel, 2009). Hence, this study attempts to explore how users actually interact with touch screen mobile phones using their fingers. We have conducted two experiments to observe and evaluate the user's finger interaction with touch screen mobile devices. The first experiment's results have indicated various problems through observation. Therefore, we developed a set of written instructions to help the users to interact better with such devices based from our observation. Another experiment was conducted to measure the effectiveness of the proposed instructions in terms of task completion time and errors occurred. The results of our study indicate that there were only minor improvements in terms of the participants' performance. As a conclusion, it is important for mobile phone designers to include user experience factors into their design. This is because a design can directly influence the user experience itself, which is vital for the success of their product.